Innocents Abroad: The Hazards of International Joint Ventures with Pyramidal Group Firms. (November 2014) - Perkins, Susan; Morck, Randall; Yeung, Bernard
<x xml:space="preserve">Abstract</x> We examine international joint ventures in the telecommunications industry in Brazil, where pyramidal groups are ubiquitous. We explain how corporate governance differences between pyramidal groups versus widely held freestanding firms can lead to joint venture failures. Our empirical results show that joint ventures between pyramidal group‐member firms and partners from countries where pyramids are rare have significantly elevated failure rates, while joint ventures with partners from countries where pyramidal groups are ubiquitous are more likely to succeed. Further, we provide clinical examples illustrating the mechanisms driving divergent partnership performance.